2013
DOI: 10.1007/s00436-013-3685-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of water extract of green propolis and liposomal meglumine antimoniate in the treatment of experimental visceral leishmaniasis

Abstract: This work investigated the use of water extract of green propolis (WEP) and its association with free or liposomal meglumine antimoniate (MA) for the treatment of murine visceral leishmaniasis. Mice infected with Leishmania infantum were treated with oral doses of WEP associated or not with a single dose of liposomal MA by intraperitoneal route. Parasite burden was assessed in the liver and spleen by limiting dilution assay, and alterations in the spleen cellular phenotype were evaluated by flow cytometry. Tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…The BP ethanolic extract and its fractions showed significant inhibition of the L. amazonensis promastigotes growth as well as were effective in reducing infection of murine macrophages and the number of internalised amastigotes in these cells. In another recente study Ferreira et al 35 showed that treatment with water extract of Brazilian green propolis was able to reduce parasite load in the liver of BALB/c mice infected with L. infantum. A comparative investigation into whether leishmanicidal activity of Brazilian and Bulgarian green propolis extracts against four different species of Leishmania was carried out by Machado et al 34 It was shown that Brazilian green propolis extract showed leishmanicidal activity for L. braziliensis, L. chagasi and L. major species with IC50 close to 49.0 μg/mL, while the Bulgarian propolis extract showed activity against L. amazonensis, L. chagasi and L. major with IC50 between 2.8 and 41.3 μg/mL.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The BP ethanolic extract and its fractions showed significant inhibition of the L. amazonensis promastigotes growth as well as were effective in reducing infection of murine macrophages and the number of internalised amastigotes in these cells. In another recente study Ferreira et al 35 showed that treatment with water extract of Brazilian green propolis was able to reduce parasite load in the liver of BALB/c mice infected with L. infantum. A comparative investigation into whether leishmanicidal activity of Brazilian and Bulgarian green propolis extracts against four different species of Leishmania was carried out by Machado et al 34 It was shown that Brazilian green propolis extract showed leishmanicidal activity for L. braziliensis, L. chagasi and L. major species with IC50 close to 49.0 μg/mL, while the Bulgarian propolis extract showed activity against L. amazonensis, L. chagasi and L. major with IC50 between 2.8 and 41.3 μg/mL.…”
Section: Resultsmentioning
confidence: 98%
“…The fact that the bees from hives located along the northeastern coast of Brazil visited D. ecastaphyllum to collect resin on the plant's surface to produce red propolis has been previously reported 12,28 . Although there is a wide range of studies related to the leishmanicidal activity of different types of propolis in different regions of Brazil and the world 20,23,[33][34][35][36][37][38][39][40] , regarding red propolis, especially the red propolis from Sergipe, there is little information available. In this way, it was evaluated for the first time the effects of different concentrations of hydroethanolic extracts obtained from red propolis from Sergipe and of the inner bark of D. ecastaphyllum on the growth of promastigotes of L. amazonensis and L. chagasi.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown antileishmanial effects in vitro and in vivo in Leishmania parasites using murine models employing propolis extracts from different sources, including propolis from Paraná, red propolis from Alagoas, and green propolis from Minas Gerais in Brazil [14, 26, 27, 4043]. …”
Section: Discussionmentioning
confidence: 99%
“…However, when Glucantime was combined with propolis, the anti-inflammatory effects became more evident. Furthermore, studies have suggested the use of propolis combined with Glucantime to decrease the side effects of Glucantime in the host (Ayres et al 2011;Ferreira et al 2014).…”
Section: Discussionmentioning
confidence: 99%